‘Swarna Shreya’ rice an aerobic variety for water-scarcity areas of central zone in India - Kumar, Santosh; Singh, S S; Dwivedi, S K; Kumar, Arvind (Indian Farming, 2018)
The released aerobic rice variety ‘Swarna Shreya’ rice showed significant yield superiority over national (CR Dhan 201), regional (MAS 946), local and hybrid (PA6129 check varieties. It was at par for most of the quality parameters in comparison to the checks. It has 56.2% head rice recovery, intermediate amylose content (21.87%), and alkali spreading value (ASV=4.0). It has high GC (65.5 mm) with very occasionally chalky and long bold grain indicating good cooking quality. This variety showed high resistance to leaf blast disease and moderately resistance to disease like neck blast, brown spot, sheath rot and RTD and insect pest like stem borer, leaf folder, gall-midge (Biotype-1) and whorl maggot. Adoption of high-yielding, goodquality input-responsive and moisture stress tolerant aerobic ‘Swarna Shreya’ rice will play proactive and decisive role in developing sustainable food production and lead for food security among farm families in the water scarcity areas in Madhya Pradesh and Chhattisgarh region of central zone in India.